Aptamer-miRNA-212 Conjugate Sensitizes NSCLC Cells to TRAIL - Margherita Iaboni; Valentina Russo; Raffaela Fontanella; Giuseppina Roscigno; Danilo Fiore; Elvira Donnarumma; Carla Lucia Esposito; Cristina Quintavalle; Paloma H Giangrande; Vittorio de Franciscis; Gerolama Condorelli (Elsevier, 2016)
TNF-related apoptosis-inducing ligand (TRAIL) is a promising antitumor agent for its remarkable ability to selectively induce apoptosis in cancer cells, without affecting the viability of healthy bystander cells. The TRAIL tumor suppressor pathway is deregulated in many human malignancies including lung cancer. In human non-small cell lung cancer (NSCLC) cells, sensitization to TRAIL therapy can be restored by increasing the expression levels of the tumor suppressor microRNA-212 (miR-212) leading to inhibition of the anti-apoptotic protein PED/PEA-15 implicated in treatment resistance. In this study, we exploited a previously described RNA aptamer inhibitor of the tyrosine kinase receptor Axl (GL21.T) expressed on lung cancer cells, as a means to deliver miR-212 into human NSCLC cells expressing Axl. We demonstrate efficient delivery of miR-212 following conjugation of the miR to GL21.T (GL21.T-miR212 chimera). We show that the chimera downregulates PED and restores TRAIL-mediate cytotoxicity in cancer cells. Importantly, treatment of Axl+ lung cancer cells with the chimera resulted in (i) an increase in caspase activation and (ii) a reduction of cell viability in combination with TRAIL therapy. In conclusion, we demonstrate that the GL21.T-miR212 chimera can be employed as an adjuvant to TRAIL therapy for the treatment of lung cancer.